(3bUjOI aj eOM GdfGUQ CHj GdYHGS CMeO Hf GdeSJYUj HGddgs - (3GHf GdJYGhjPj, eMeO Hf YHjO Gddg Hf YHO Gddg, J(B583(3g`s
(3ChdgG (B:s
(3SbGc SGQ ef GdhSej gJGf (B*** (3hdG QbJ ddZhGfj ajc CLaGfs
(3BNQgG (B:s
(3hGSde JOhe dc GdfYeGA aEfc eG (B*** (3SdeJ aj LOd aGdOgQ LOdGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 260s
(3eYLe GdeDdajf(B: 3 / 478s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs